2006
DOI: 10.1002/rcm.2794
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of trandolapril and its metabolite trandolaprilat in human plasma by liquid chromatography/tandem mass spectrometry using solid‐phase extraction

Abstract: A sensitive high-performance liquid chromatography/electrospray ionization tandem mass spectrometry (MS/MS) method was developed and validated for the simultaneous quantification of trandolapril and its metabolite trandolaprilat in human plasma using ramipril as an internal standard. Following solid-phase extraction, the analytes were separated using an isocratic mobile phase on a reversed-phase column and analyzed by MS/MS in the multiple reaction monitoring mode using the respective [M-H]- ions, m/z 429/168 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…An HPLC-MS/MS assay was developed to determine concentrations of the trandolapril active metabolite, trandolaprilat, based on a previously published method with some modifications [11]. The HPLC-MS/MS analytical system consisted of a Shimadzu Prominence HPLC system and an Applied Biosystems API 4000 QTRAP ® mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…An HPLC-MS/MS assay was developed to determine concentrations of the trandolapril active metabolite, trandolaprilat, based on a previously published method with some modifications [11]. The HPLC-MS/MS analytical system consisted of a Shimadzu Prominence HPLC system and an Applied Biosystems API 4000 QTRAP ® mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Le bilan biologique d'entrée révélait la présence d'une acidose (pH 7,17, valeurs normales (7,45)) lactique (lactate à 4,9 mmol/L (0,5-2)), d'une hyperkaliémie à 5,9 mmol/L (3,5) …”
Section: Observationunclassified
“…Après contact avec le laboratoire fabriquant, le dosage de ce médicament se fait par immuno-histochimie. Une méthode de dosage par CLHP-SM/SM a été initiée [3] mais son intérêt demeurait limité du fait d'un stockage important de ce médicament dans les tissus. Ainsi, la quantification sérique n'a pas été réalisée.…”
Section: Résultatsunclassified
“…Also there is a method reported in the literature to measure trandolapril in human plasma by tandem mass spectrometry [18]. The method was successfully applied for quantification of trandolapril and its metabolite trandolaprilat in human plasma by liquid chromatography/tandem mass spectrometry using solid-phase extraction [19]. Mass spectral fragmentation reactions of ACE inhibitors [20] and a study on the stereochemical purity of trandolapril were also reported [21].…”
Section: Introductionmentioning
confidence: 98%
“…A number of high performance liquid chromatography (HPLC) [19][20][21] and mass spectrometry analysis methods have been reported for this drug. However, the study of degradation behavior of trandolapril by UPLC under various ICH prescribed stress conditions has been lacking.…”
Section: Introductionmentioning
confidence: 99%